Salivary‐secreted vitellogenin suppresses H2O2 burst of plants facilitating Recilia dorsalis leafhopper feeding - Lu, Chengcong; Zhang, Yating; Xu, Yuanyuan; Wei, Taiyun; Chen, Qian (Pest management science, 2024)
BACKGROUND Vitellogenin (Vg), known as the yolk protein precursor for oocyte development in female insects, can be secreted to plant host from salivary glands of hemipterans, including rice leafhopper Recilia dorsalis. The aim of this study was to investigate the function of salivary‐secreted Vg of R. dorsalis (RdVg) in rice host. We propose that RdVg possibly regulates the rice defense against insects, benefiting R. dorsalis feeding. RESULTS RdVg was released into rice phloem along with saliva during R. dorsalis feeding. Knocking down RdVg increased the level of H2O2 and improved H2O2 metabolism in rice plants, making it difficult for R. dorsalis to feed. The transient expression or overexpression of the lipoprotein N‐terminal domain of RdVg (RdVg2) significantly reduced hydrogen peroxide (H2O2) metabolism in plants. This suggests that salivary‐secreted RdVg acts as an effector suppressing the H2O2 burst in rice plants, and RdVg2 is the key domain. RdVg2 could interact with rice sulfite oxidase (OsSO), which catalyzes the oxidation of SO32− and produces H2O2. Exposure of rice plants to R. dorsalis, overexpression of RdVg2 or knocking out OsSO reduced OsSO accumulation and SO32− oxidation, benefiting R. dorsalis feeding. However overexpression of OsSO increased SO32− oxidation and H2O2 metabolism, inhibiting R. dorsalis feeding. CONCLUSION RdVg inhibits H2O2 generation via suppressing OsSO accumulation, ultimately benefiting R. dorsalis feeding. These findings identify RdVg as an effector that suppresses plant defense to insects, and provide insights into the function of salivary‐secreted Vg in other Hemiptera insects. © 2024 Society of Chemical Industry. Salivary‐secreted vitellogenin of leafhopper Recilia dorsalis (RdVg) is released into the phloem during R. dorsalis feeding. RdVg in rice plant functions as an effector suppressing rice sulfite oxidase via interaction to inhibit the H2O2 burst of rice, thus benefiting R. dorsalis feeding.